2017
DOI: 10.1007/s00412-017-0654-5
|View full text |Cite
|
Sign up to set email alerts
|

Photoconversion of DAPI and Hoechst dyes to green and red-emitting forms after exposure to UV excitation

Abstract: The fluorescent dye 4'-6-Diamidino-2-phenylindole (DAPI) is frequently used in fluorescence microscopy as a chromosome and nuclear stain because of its high specificity for DNA. Normally, DAPI bound to DNA is maximally excited by ultraviolet (UV) light at 358 nm, and emits maximally in the blue range, at 461 nm. Hoechst dyes 33258 and 33342 have similar excitation and emission spectra and are also used to stain nuclei and chromosomes. It has been reported that exposure to UV can convert DAPI and Hoechst dyes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…A variety of DNA binding dyes, such as DAPI and Hoechst can change their optical properties upon exposure to light 1, 2 . This process, termed photoconversion, can occur during multicolor fluorescence microscopy and may lead to false-positive signals 2, 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of DNA binding dyes, such as DAPI and Hoechst can change their optical properties upon exposure to light 1, 2 . This process, termed photoconversion, can occur during multicolor fluorescence microscopy and may lead to false-positive signals 2, 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to UV or to low pH, the emission spectra of DAPI and Hoechst shift from the blue to the green wavelength with detectable signals in the yellow, orange and red wavelengths 1, 2, 4, 5 . This shift makes the signal indistinguishable from the emission of other standardly used fluorescent proteins such as GFP.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of photoconversion of DAPI and similar dyes may vary depending on instrument configuration. While photoconversion of DAPI can become apparent after a few seconds [2], detection of intense photoconversion product fluorescence more commonly requires continuous UV irradiation for 30 seconds or longer [1,3,6]. Photoconversion artifacts can be avoided by keeping UV excitation of DAPI as brief as possible when locating and focusing on specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Photoconversion has been reported for DAPI, Hoechst dyes, and Vybrant® DyeCycle™ Violet in the presence or absence of DNA [5]. Multiple groups reported that the appearance of photoconversion products correlated with the photobleaching of blue fluorescence and that while blue fluorescence recovered over time in the dark, the photoconversion products did not disappear completely [3,5,6]. Żurek-Biesiada and colleagues examined the chemical mechanisms of photoconversion.…”
Section: Introductionmentioning
confidence: 99%
“…Its excitation/emission spectra do not overlap with other commonly used small-molecule fluorophores and fluorescent proteins that emit in the green-red range. In addition, there have been recent reports that exposure of Hoechst 33258 and Hoechst 33342 to UV light results not only in bleaching, but also in photoconversion to species with excitation/emission in the blue/green and green/red range [19,20]. This property was employed in single-molecule localization microscopy to obtain higher resolution DNA maps [21].…”
Section: Properties Of Hoechst Dyesmentioning
confidence: 99%